Respuesta :

Answer:

the mistake is in second step

Step-by-step explanation:

Correct Answer is :

12(5+2y)= 4y- (5-9y)

60+24y= 4y-5+ 9y

60+24y= -5+13y

60+5= 13y-24y

65= -11y

65/-11= y

Answer: y = -65/11

Step-by-step explanation:

12 ( 5 + 2y) = 4y - (5 - 9y)

60 + 24y = 4y - 5 - 9y

↑This is where she made the mistake

When you distribute - 1 to 5 and -9y, you multiply -1 by both expressions

-1 × 5 = -5

-1 × -9y = + 9y

She wrote - 9y not + 9y when it should be + 9y cuz negative × negative is positive.

The correct solution to the equation

12 ( 5 + 2y) = 4y - (5 - 9y)

60 + 24y = 4y - 5 + 9y

Subtract 60 from both sides

24y = 4y - 5 + 9y - 60

24y = 13y - 65

Subtract 13y from both sides

11y = -65

Divide 11 from both sides

y = -65/11